Hubungan Anemia Defisiensi Besi dengan Status Gizi Anak Usia 0–17 Tahun di RSUD Dr. Pringadi Medan 2023–2024 - Eva Uwari Situmorang; Siti Aisyah Dalimunthe; Irza Haicha Pratama (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Iron deficiency anemia (IDA) remains a major nutritional problem among children in developing countries, significantly affecting health, growth, and development. IDA occurs when hemoglobin levels decrease due to insufficient iron intake, thereby limiting oxygen distribution to body tissues. This study aimed to analyze the relationship between IDA and nutritional status among children aged 0–17 years treated at Dr. Pringadi General Hospital Medan during 2023–2024. A cross-sectional analytic design was employed with a population of 76 children, and 64 samples met the inclusion criteria. Data were collected from medical records, including hemoglobin levels, body weight, height, age, and gender. Statistical analysis was conducted using the chi-square test with SPSS. Results showed that the prevalence of IDA was 84.4% (54 children), while poor nutritional status was found in 51.6% (33 children). Statistical testing confirmed a significant association between IDA and nutritional status (p = 0.018 < 0.05). These findings emphasize the close link between anemia and malnutrition in influencing child growth and development, although not all children with IDA were undernourished. This suggests the involvement of other factors such as parenting practices, dietary diversity, and infection status. The study recommends comprehensive interventions, including nutrition education, iron supplementation, improved dietary quality, and continuous nutritional monitoring, to reduce the prevalence of IDA and malnutrition, thereby supporting healthier and more productive future generations.